Mamanda theatre, the play of Banjar culture - Kleden-Probonegoro, Ninuk (Wacana, Journal of the Humanities of Indonesia, 2010)
This article reveals the dialectic relationship between Teater Mamanda and the living conditions of Banjarese community. When we watch Mamanda, we watch the life and culture of the Banjarese. Without any knowledge of Banjarese society and culture we cannot possibly understand the content of a Mamanda performance as a miniature version of Banjarese society and culture. Three areas where Mamanda is performed have been studied using Paul Ricoeur's textual theory. There are two kinds of texts, the Mamanda performance (considered as text, that is, social events fixated in the form of a performance), and the narration of the performance itself which is considered a text as well.